The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2478/adms-2014-0020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microstructural Changes of S235 Steel after Rolling on the Basis of Microscopic Observations and Eddy Current Non-Destructive Method

Abstract: The aim of the study was to determine the microstructure and residual stress changes which appears in the S235 steel (which is designed for operating in elevated temperatures) during cold rolling. The changes of orientation, both morphological and crystallographic, are occurring as a result of the rolling process. Analysis of the results allowed to determine the change in grain morphology (size, shape), determination of grain morphology of the rolling direction and determination of crystallographic texture. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Skutkuje to ograniczeniem głębokości wnikania prądów w stali ferromagnetycznej do kilkuset mikrometrów, czyli w zakresie grubości warstw hartowanych. Podobne badania, z zastosowaniem prądów wirowych prowadzono także w zakresie oceny stopnia uszkodzenia zmęczeniowego [1,2], stanu składowych naprężenia resztkowych [3], czy też grubości warstw hartowanych [4,5]. Z kolei metoda szumów Barkhausena wykorzystywana była przez autorów m in.…”
Section: Materiał I Metodykaunclassified
“…Skutkuje to ograniczeniem głębokości wnikania prądów w stali ferromagnetycznej do kilkuset mikrometrów, czyli w zakresie grubości warstw hartowanych. Podobne badania, z zastosowaniem prądów wirowych prowadzono także w zakresie oceny stopnia uszkodzenia zmęczeniowego [1,2], stanu składowych naprężenia resztkowych [3], czy też grubości warstw hartowanych [4,5]. Z kolei metoda szumów Barkhausena wykorzystywana była przez autorów m in.…”
Section: Materiał I Metodykaunclassified
“…It was identified that quality check results are mostly requested from the sugar industry, while a precise specification of the final product is hardly requested [13]. Several destructive/non-destructive techniques are reported in literature, focusing on the major causes that lead to defective production, such as magnetic particle testing [14], ultrasonic testing [15], crystallographic testing [16] and scanning electron microscopy (SEM). The in-depth porosity effect on the fatigue life of the A319 alloy was discussed by Zhang et al [17].…”
Section: Introductionmentioning
confidence: 99%